2018
DOI: 10.1080/10428194.2018.1474521
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of HLA-E genotype and surface/soluble expression levels between healthy individuals and patients with acute leukemia

Abstract: Human leukocyte antigen (HLA)-E is a nonclassical HLA molecule with limited polymorphisms. Genotype frequency and expression of HLA-E were examined here for the first time in acute leukemia patients and healthy controls. The frequency of HLA-E*01:03/*01:03 individuals was significantly higher (p = .008, OR = 1.845), while the frequency of HLA-E*01:01/*01:01 individuals was much lower in the patient group (p = .002, OR = .363) than in control group. The surface expression on HLA-E*01:03/*01:03 individuals was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Women carrying the HLA-E G allele are more susceptible to serous ovarian cancer [72]. HLA-E G homozygous genotype is associated with significantly higher risk of acute leukemia and higher level of sHLA-E in the patient group [73]. Among nasopharyngeal carcinoma patients, HLA-E G allele was significantly more frequent than HLA-E R [74].…”
Section: Hla-e Dimorphism and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Women carrying the HLA-E G allele are more susceptible to serous ovarian cancer [72]. HLA-E G homozygous genotype is associated with significantly higher risk of acute leukemia and higher level of sHLA-E in the patient group [73]. Among nasopharyngeal carcinoma patients, HLA-E G allele was significantly more frequent than HLA-E R [74].…”
Section: Hla-e Dimorphism and Cancermentioning
confidence: 99%
“…Hirankarn with colleagues suggested that HLA-E R could be beneficial for antitumor immune responses due to lower surface expression of HLA-E*01:01, which results in lower inhibitory action for CD94 + /NKG2A + immune cells [74]. Also, two reports indicated the association between HLA-E G and the level of sHLA-E in patients’ sera [59,73]. As discussed earlier, sHLA-E provides the protection of cells from NK-mediated lysis.…”
Section: Hla-e Dimorphism and Cancermentioning
confidence: 99%
“…The Japanese encephalitis virus, a flavivirus responsible for encephalitis in Asian children, upregulates HLA-E cell-surface levels, coupled to an enhanced release of sHLA-E, suggesting a potential immuno-evasive strategy likely developed by the viral agent against host mediated immune responses 27 . In cancer, whilst high sHLA-E levels associate with a better overall survival in neuroblastoma 28 , high sHLA-E levels were also observed: (i) in advanced stages of chronic lymphocytic leukemia, with sHLA-E levels decreasing after treatment 29 ; and (ii) in patients suffering from acute leukemia, as compared to healthy controls 30 . Finally, in melanoma, several studies show high sHLA-E levels to be released by neo-transformed melanocytes 31 , a finding at the origin of the recent development of a novel immune check point inhibitor targeting the HLA-E specific NKG2A inhibitory receptor, namely Monalizumab 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HLA-G, HLA-E expression can be observed in multiple cancer entities such as breast cancer [132], colorectal cancer [158,159,160,201], renal cancer [173,202,203], lung cancer [204], melanoma [205,206], and gastric cancer [207,208], cervical cancer (adenocarcinoma) [209], glioblastoma [174,177,210], Hepatic carcinoma (hepatocellular) [211], Hodgkin’s lymphoma [212], Thyroid cancer [213] and leukemia [214]. Table 3 shows an overview of tumors in which expression of HLA-E has been detected.…”
Section: “Embryonic“ Hla Genes In Tumorsmentioning
confidence: 99%